Scrub typhus-associated Kawasaki disease in a toddler: An uncommon infectious trigger of systemic vasculitis - mujalda, jagdish; abha kumari, Abha kumari; Takkar, Pranav; Katyal, Amit (Indian Journal of Case Reports, 2026)
Kawasaki disease (KD) is an acute medium‑vessel vasculitis and a leading cause of acquired heart disease in children. Scrub typhus may mimic KD or coexist, requiring prompt antibiotic therapy, while KD necessitates immunomodulatory treatment. Careful clinical evaluation, laboratory assessment, and echocardiography are essential for differentiation. A systematic, multidisciplinary approach improves diagnostic accuracy, optimizes management, and reduces cardiovascular complications. We report a 2‑year‑10‑month‑old boy who presented with high‑grade fever, generalized maculopapular rash, and bilateral non‑purulent conjunctival congestion. Based on clinical features consistent with KD, he was promptly treated with intravenous immunoglobulin and aspirin to reduce the risk of coronary artery complications, resulting in initial defervescence and clinical improvement. However, recurrence of fever during hospitalization necessitated further evaluation for alternative or concomitant etiologies. Subsequent laboratory investigations revealed positive serology for scrub typhus. Doxycycline therapy was initiated, leading to sustained defervescence and complete recovery. This case emphasizes the importance of early diagnosis and timely management of KD to prevent cardiac sequelae. It also highlights the need to consider coexisting tropical infections, particularly in an endemic region, in children with persistent or recrudescent fever despite appropriate initial immunomodulatory therapy.